Jews and Muslims in the Works of John of Naples. - Schut, Kirsten (Medieval Encounters, 2019)
This article seeks to shed light on attitudes towards Jews and Muslims in the Kingdom of Naples during the early fourteenth century by examining references to non-Christians in the quodlibets, disputed questions, and sermons of the Dominican theologian John of Naples (Giovanni Regina, d. ca. 1348). John's patron, King Robert of Naples (r. 1309–1343) has traditionally been portrayed as a more tolerant monarch than his predecessor Charles II, and John's views seem to accord well with Robert's: he does not advocate conversion, but rather allows Jews and Muslims a limited place within Christian society. Treating topics as diverse as biblical exegesis, blasphemy, sorcery, slavery, mercenaries, and medical ethics, John's writings on Jews and Muslims were inspired both by traditional scholastic questions and contemporary events. While his views on non-Christians are far from positive, John stops short of disseminating the more virulent polemics of his time.